ARCHAEOLOGICAL DISCOVERIES IN HUACA HUANTILLE OF LOWER RIMAC VALLEY, DURING THE LATE INTERMEDIATE - Guillén Hugo, Marco (2012)
The monument is known for its construction on the basis of mud walls, which were used as a large terrace for its facade, which gave a morphology of a truncated pyramid that reached a height of 16 m, and the use of double-sided thick walls for their indoor enclosures, located at the top of the building., most painted white. The plant enclosures are orthogonal, and a very characteristic sign is the architectural element of bench or floor spaces L ceremonial use. The rooms were filled and then build on these, in order to gain volume, until the final dimension.